Case report: Delayed quadriplegia from traumatic carotid cavernous fistula: a rare case with perimedullary venous drainage - Ma, Yu-Hu; Shang, Rui; Lin, Sen; Li, Si-Hao; Wang, Ting; Zhang, Chang-Wei (Frontiers in Neurology, 2023)
Background Carotid cavernous fistula (CCF) refers to the abnormal arteriovenous communication between the carotid system at the skull base and the sphenoid cavernous sinus, which is caused by trauma in almost 75% of cases. The drainage of venous blood to the spinal cord represents a distinctive mechanism, which is commonly observed in dural arteriovenous fistula (DAVF), and typically manifests clinically as progressive myelopathy. However, it is a rare occurrence in clinical practice that traumatic carotid cavernous fistula (TCCF) causes delayed quadriplegia through perimedullary venous drainage. Case presentation We report the case of a 29-year-old male patient who was admitted to the hospital with a sudden onset of headache and quadriplegia. The patient had previously lost his right eye in a traffic accident 5 years ago. Cerebral angiography showed a high-flow direct CCF on the right side, accompanied by obvious drainage of cerebellar and perimedullary veins. We successfully performed coil embolization for the CCF, and the symptoms of the patient gradually improved after the operation. During follow-up at sixth-months, the patient regained the ability to walk independently. Conclusion We experienced a rare case of TCCF with quadriplegia. Utilizing coil embolization, we achieved successful improvement in the patient’s condition. However, the mechanism and the best treatment of CCF drainage through the perimedullary vein are still unclear. We need to further explore the pathophysiological information of CCF venous drainage.